Resistance pattern of mupirocin in methicillin-resistant Staphylococcus aureus in trauma patients and comparison between disc diffusion and E-test for better detection of resistance in low resource countries - Rajkumari, Nonika; Mathur, Purva; Bhardwaj, Nidhi; Gupta, Gunjan; Dahiya, Rajrani; Behera, Bijayini; Misra, Mahesh Chandra (Journal of Laboratory Physicians, 2014)
Introduction: Mupirocin is an effective antibiotic for elimination of methicillin-resistant Staphylococcus aureus (MRSA) from nasal colonization and has been used to control outbreaks. Current reports show an increasing trend of resistance to this antibiotic.Objective: This study was conducted to analyze the resistance pattern of MRSA to mupirocin among the patients admitted following trauma to an apex trauma care center of India and to compare the efficacy between two methods of antimicrobial sensitivity testing.Materials and Methods: A total of 150 isolates of MRSA from various clinical samples of trauma patients over a period of 2 years were included in this study. These strains were confirmed for MRSA using VITEK ® 2 Compact and the Clinical Laboratory Standard Institute disc diffusion methods. The mupirocin susceptibility of the strains was tested by using E-test and 5 μg mupirocin disc in parallel each time, and the results were compared.Results: Clear zones of inhibition were observed in both tests. Though, good correlation was observed between the disc diffusion and E-tests in >98%, E-test showed a tendency to show lower minimum inhibitory concentration (MIC) in the remaining. These finding did not affect the final interpretation or outcomes. Of the total 150 strains, 138 (92%) showed sensitivity with the zone size in the range of 30-45 mm by 5 μg disc; rest (8%) showed sensitivity with the zone in the range of 18-30 mm by 5 μg disc, but 143 (95%) showed MIC ≤ 0.094 μg/ml and 8 (5%) gave MIC ≤ 0.75 μg/ml but ≥0.094 μg/ml by E-test. However, when both tests were compared, 5 (3.3%) showed zone size between 14 and 25 mm with ≤0.75 but >0.25 μg/ml MIC; 7 (5%) falling between 25 and 30 mm zone with MIC of ≤0.25 but >0.094 μg/ml and 138 (92%) showed zone >30 mm with MIC ≤0.094 but >0.064 μg/ml.Conclusions: All the MRSA isolates in our study were sensitive to mupirocin which is an encouraging finding. Though good screening for sensitivity can be done with 5 μg mupirocin disc, E-test provides a much clear and accurate results in clinical set-up. Hence, disc test can be used in resource poor countries and supplemented with E-test when needed.
Keywords: Antibiotic resistance; disc diffusion; E-test; methicillin-resistant Staphylococcus aureus; mupirocin